Німецько-фашистський окупаційний режим на Волині в роки Другої світової війни - Ленартович, Олег Юрійович; Lenartovich, Oleg Y. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті розглянуто питання формування системи окупаційної влади на Волині в роки Другої світової війни, визначено засоби її реалізації, причини появи руху Опору нацистам. The first scientific papers devoted to the study of the damage inflicted on Ukraine during the German occupation, the numbers involved loss of population, the study plans Nazis against the Slavic population and means of implementation. A striking example of Soviet historiography devoted to issues of economic plunder Ukraine by the Nazis, is working Zagorulko M. and A. Yushchenko’s «collapse plan» Oldenburg "published in Moscow in 1980.
German-Nazi occupation Regime in Volyn during the Great Patriotic War
Keywords: окупація; рейхскомісаріат «Україна»; Волинь; геноцид; податки; occupation; reyhskomisariat «Ukraine»; Volhynia; genocide; taxes